Concreto celular polimérico: influência na adição de resíduo de poliéster insaturado termofixo - Melo, Guilherme Fábio de (2009)
This work addresses the production of lightweight concrete building elements, such as plates, prefabricated slabs for pre-molded and panels of fencing, presenting a singular concrete: the Lightweight Concrete, with special properties such low density and good strength, by means of the joint use of industrial waste of thermosetting unsaturated polyesters and biodegradable foaming agent, named Polymeric Lightweight Concrete. This study covered various features of the materials used in the composition of the Polymeric Lightweight Concrete, using a planning of factorial design 23, aiming at studying of the strength, production, dosage processes, characterization of mechanical properties and microstructural analysis of the transition zone between the light artificial aggregate and the matrix of cement. The results of the mechanical strength tests were analyzed using a computational statistics tool (Statistica software) to understand the behavior and obtain the ideal quantity of each material used in the formula of the Polymeric Lightweight Concrete. The definition of the ideal formula has the purpose of obtaining a material with the lowest possible dry density and resistance to compression in accordance with NBR 12.646/92 (≥ 2.5 MPa after 28 days). In the microstructural characterization by scanning electron microscopy it was observed an influence of the materials in the process of cement hydration, showing good interaction between the wrinkled face of the residue of unsaturated polyesters thermosetting and putty and, consequently, the final strength. The attaining of an ideal formula, given the Brazilian standards, the experimental results obtained in the characterization and comparison of these results with conventional materials, confirmed that the developed Polymeric Lightweight Concrete is suitable for the production of building elements that are advantageous for construction